Promising High Value Fruit Crops for Northeastern Region - Karunakaran, G; Arivalagan, M; Sakthivel; Tripathi, P C; Kumar, Pushpa Chethan; Shameena, A; Ruchitha, T; Muralidhara, B M (Indian Horticulture, 2024)
Among the high value fruit crops, jackfruit, passion fruit, dragon fruit and avocado holds prime position for diversification as a commercial crop. The present market appeal and demand, growers’ interests and consumers preference indicate that high value fruits have good potential for commercial exploitation in the near future; hence needs due attention. At present, the major market demand for these crops is from metropolitan cities in India, and market prices for these fruits varies between ` 150-300 per kg depending upon the grade and quality. Northeastern region has high potential of international quality grade fruits crops to produce with the bio diversity and suitable climate.